2016
DOI: 10.5935/1981-2965.20160050
|View full text |Cite
|
Sign up to set email alerts
|

Profile of lactic acid within validity of full natural yogurt

Abstract: pH and acidity analyzes were performed in the 15th, 30th and 45th day after the manufacture of the product. The results showed that there were no significant variations in the pH values. However, the lactic acid had greater variability in values. Despite this, all the tests remained within acceptable parameters for yogurt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Pimentel et al, (26) also reported similar behaviours in the pH and acidity values demonstrating a drop in the pH (from 4.45 to 4.24) and a spike in the acidity (from 1.11 to 1.17%) in their study on the effect of storage on probiotic skimmed-milk yoghurt for 28 days. Silva et al, (27) also recorded a decrease in the pH values (from 4.01 to 3.89) and a rise in the acidity (from 0.98-1.18%), although neither exerted a significant effect during 45-day storage period of the yogurt. Earlier, Araújo et al, (28) had identified pH values of 4.85 in the goat milk yoghurts.…”
Section: Resultsmentioning
confidence: 92%
“…Pimentel et al, (26) also reported similar behaviours in the pH and acidity values demonstrating a drop in the pH (from 4.45 to 4.24) and a spike in the acidity (from 1.11 to 1.17%) in their study on the effect of storage on probiotic skimmed-milk yoghurt for 28 days. Silva et al, (27) also recorded a decrease in the pH values (from 4.01 to 3.89) and a rise in the acidity (from 0.98-1.18%), although neither exerted a significant effect during 45-day storage period of the yogurt. Earlier, Araújo et al, (28) had identified pH values of 4.85 in the goat milk yoghurts.…”
Section: Resultsmentioning
confidence: 92%
“…Por meio dos dados apresentados, observou-se que a acidez de ambos os iogurtes tendeu a aumentar ao longo do tempo de armazenamento, com regressão significativa (pr(t) <0,05) para o iogurte com corante (R 2 = 0,4184) e para o sem corante (R 2 = 0,5314). Tal fato é esperado para iogurtes, fenômeno conhecido como pós-acidificação, e ocorre devido à manutenção da atividade metabólica das bactérias lácticas mesmo à temperatura de armazenamento, podendo ocorrer até pelo menos quatro semanas após a fabricação (Coelho et al, 2009;Silva et al, 2016). O fato descrito também explica a variação do pH ocorrida, no entanto com correlação significativa somente para o iogurte sem corante (R 2 = 0,6916).…”
Section: Avaliação Das Características Dos Iogurtes Durante O Armazen...unclassified